Performance, sizing, and residual load – an analysis of photovoltaic systems for a water treatment facility - Liberski, Thomas; Canales, Fausto A.; Jurasz, Jakub (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This study presents an analysis of photovoltaic (PV) systems designed for a water supply utility located in the Lower Silesian Voivodeship, Poland, focusing on system sizing, configurations, and residual load implications. The analysis has two key objectives: maximizing the capacity factor and self-consumption and then comparing both cases using residual load. Using hourly electricity demand data from eight locations, along with satellite-based solar irradiance and weather inputs, the research identifies optimal tilt and azimuth configurations under both objectives. The findings reveal that capacity factor optimization yields annual capacity factor values ranging from 13.00% to 13.38%, but results in lower self-consumption rates (ranging from 33.39% to 46.59%). In contrast, self-consumption optimization produces higher levels (ranging from 35.11% to 47.39%) but leads to reduced capacity factor performance (ranging from 6.93% to 11.57%). A centralized PV system configuration is also evaluated, achieving a capacity factor of 13.27% and self-consumption of 42.08% in the capacity factor optimized case, and 6.93% capacity factor with 44.84% self-consumption in the self-consumption optimized case. The results highlight a trade-off between maximizing energy yield and improving temporal matching of generation and demand, with each optimization strategy enhancing a different aspect of PV system performance in electricity supply for the critical infrastructure operation.